Validation and clinical application of a novel LC–MS method for quantification of dolutegravir in breast milk. (19th November 2018) - Gini, Joshua; Penchala, Sujan Dilly; Amara, Alieu; Challenger, Elizabeth; Egan, Deirdre; Waitt, Catriona; Lamorde, Mohammed; Orrell, Catherine; Myer, Landon; Khoo, Saye; Else, Laura J
Aim: A novel, sensitive and reproducible method for quantification of dolutegravir (DTG) in dried breast milk spots (DBMS) was developed and validated for use in clinical studies. Its application enabled measurement of DTG pharmacokinetics in breastfeeding mothers and their infants.Results/methodology: Sample extraction was by liquid–liquid extraction using tert-butyl methy-ether, with DTG–d5 as an internal standard. DTG was eluted on a reverse phase C18 Waters XBridge (3.5 μm: 2.1 × 50 mm) column using a gradient mobile phase consisting of 0.1% formic acid in deionised water or methanol. The assay was validated over a calibration range of 10–4000 ng/ml.Conclusion: Stability, inter and intra-assay variability were acceptable according to FDA and EMA bioanalytical method guidelines. The assay is robust, accurate, precise and can be reliably applied for analysis of clinical samples in trials from low resource settings.